Transition-Metal-Catalyzed Enantioselective α-Arylation of Carbonyl Compounds to Give Tertiary Stereocenters - Orlandi, Manuel; Escudero-Casao, Margarita; Licini, Giulia (Synthesis, 2021)
Enantioenriched α-aryl carbonyl compounds are ubiquitous in natural products and biologically active compounds. Their synthesis has been explored over the last few decades and several methods now exist that allow for the enantioselective formation of a C(sp3)-C(sp2) bond in the α-position to a carbonyl group. However, although the formation of quaternary stereocenters has been fairly well established, the enantioselective formation of tertiary stereocenters proved more challenging due to facile product post-reaction racemization. In this short review, we summarize the methods reported to date for the asymmetric α-arylation of enolates and analogues that rely on transition-metal catalysis.1 Introduction2 Nucleophile Pre-activation3 Activation via Aminocatalysis4 Formation of Constrained Stereocenters5 Concluding Remarks
Keywords: α-arylation of carbonyl compounds; transition-metal catalysis; enantioselective catalysis; aminocatalysis; tertiary stereocenters